Optimization or Bricolage? Overcoming Resource Constraints in Global Social Entrepreneurship - Desa, Geoffrey; Basu, Sandip (Strategic Entrepreneurship Journal, 2013)
Resources play a vital role in the development of an entrepreneurial venture. For ventures operating in the public interest, the process of effective resource mobilization can be especially critical to the social mission. However, there has been limited empirical examination of the approaches used by social ventures to mobilize critical resources. We study two processes of resource mobilization—optimization and bricolage, and examine the antecedent conditions that influence a venture's selection of these processes. Our theory predicts that environmental munificence and organizational prominence have U‐shaped associations with the use of bricolage and positive associations with the use of optimization. We test our hypotheses on a sample of 202 technology social ventures from 42 countries and discuss implications for the social entrepreneurship and broader entrepreneurship literatures. Copyright © 2013 Strategic Management Society.